The goat semen quality after being frozen using albumin and cholesterol substituted for egg yolk in semen extender - Terdchai Kaewkesa (2018)
The objective of this study was to determine the effect of albumin and cholesterol substituted for egg yolk in goat semen extender after frozen-thawed on semen quality and pregnancy rate. The semen was collected from three bucks by using artificial vagina. The semen was divided into 5 groups; in group 1, seminal plasma was removed and 20% egg yolk extender was added (standard), in group 2, 2% egg yolk extender was added into whole semen (control), in group 3, 4 mg/mL albumin extender was added into whole semen, in group 4, 5 mg/mL cholesterol extender was added into whole semen, and in group 5, 4 mg/mL albumin and 5 mg/mL cholesterol extenders were added into whole semen. Semen was loaded into 0.25 mL straw and frozen by automatic semen freezing machine and stored in liquid nitrogen. The frozen semen was thawed at 37 °C for 30 seconds. It was found that the cholesterol-added group was not different from the standard control group but the albumin or the albumin-cholesterol-added groups were significantly lower (P < 0.05) than both control groups when compared with microscopic semen quality, computer analyzed semen quality. The result of pregnancy rate by artificial insemination with frozen semen was not significantly different but tended to be lower in the albumin-added group. In conclusion, cholesterol-added extender substituted egg yolk in whole goat semen prove to be of practical use.